Ritual as mechanism for securing life and averting evil among the Krobo - G. Ossom-Batsa (Acta Theologica)
Ritual is one of the ways in which a group of people or a believing community expresses in concrete terms their faith in a deity(ies). Two of the many functions of rituals are to secure blessings from the deity or to ward off evil. This article studies four Krobo rituals to explore the ultimate meaning of life in Krobo worldview: material and spiritual wellbeing. The fight against sickness, misfortune, evil and other disasters provides the framework within which they express their dependence on their creator by means of rituals. To the Krobo life without the divinity cannot attain its fullness; hence the constant appeal to the divinities for protection and blessings.